PENERAPAN METODE MUHADATSAH DALAM MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB DI PESANTREN SAHABAT QURAN - Muhammad Solihin Pranoto; Rahmi Utami; Abd Mukti; Mawarda Mawarda (UIN Sumatera Utara Medan, 2025)
This study aims to examine the implementation of the muhadatsah method in improving Arabic speaking skills at Pesantren Sahabat Quran, identify the supporting and inhibiting factors in its application, and evaluate the effectiveness of the method. This research employs a qualitative approach with a case study method, involving active students, Arabic teachers, and pesantren administrators as informants. Data collection techniques include participatory observation, in-depth interviews, and documentation, while data analysis uses the interactive model of Miles and Huberman. The results show that the muhadatsah method is intensively applied through active conversational practice, which encourages improvements in fluency, vocabulary enrichment, and understanding of Arabic sentence structures. The main supporting factors are a conducive learning environment and student motivation, while limited practice time and low self-confidence become obstacles. Overall, the muhadatsah method is proven effective in enhancing Arabic speaking skills among students at Pesantren Sahabat Quran.